2020
DOI: 10.1039/d0nr02581j
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinting of cell-laden electroconductive MXene nanocomposite bioinks

Abstract: MXenes, a new family of two-dimensional transition metal carbides/nitrides, have been exploited in 3D bioprinting owing to their outstanding properties such as a large specific surface area, high electrical conductivity, and biodegradability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 59 publications
0
88
0
Order By: Relevance
“…Geometrical properties of MXene (Ti 3 C 2 T x ) monolayers have been studied extensively. The results [9,11] of morphology and characterization of MXenes (Ti 3 C 2 T x ), developed in the last few years obtained using a synthesis process of in-situ hydrogen fluoride (HF) formation with the minimally intensive layer delamination (MILD) method, indicate an average lateral dimension of MXene (Ti 3 C 2 T x ) monolayers to be in the range of a few microns (1-12 µm, without sonification) and the thickness to be in the range of few nanometers (1-10 nm) [39]. Lateral dimensions of 2 microns and a thickness of 2 nm is used for all the MXene monolayer models in this paper.…”
Section: Mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometrical properties of MXene (Ti 3 C 2 T x ) monolayers have been studied extensively. The results [9,11] of morphology and characterization of MXenes (Ti 3 C 2 T x ), developed in the last few years obtained using a synthesis process of in-situ hydrogen fluoride (HF) formation with the minimally intensive layer delamination (MILD) method, indicate an average lateral dimension of MXene (Ti 3 C 2 T x ) monolayers to be in the range of a few microns (1-12 µm, without sonification) and the thickness to be in the range of few nanometers (1-10 nm) [39]. Lateral dimensions of 2 microns and a thickness of 2 nm is used for all the MXene monolayer models in this paper.…”
Section: Mxenesmentioning
confidence: 99%
“…Almost immediately, MXenes attracted a great deal of interest in various fields of applications due to their unique physical properties such as good conductivity [8], film-forming ability and good elasticity [9]. Moreover, it has been reported that MXenes are environmental friendly materials (low toxicity [10] and biodegradable [11]), thus showing their potential in biosensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…65 Innovative cell-laden bioink encompassing electroconductive Ti 3 C 2 MXene nanosheets were created and uniformly dispersed in hydrogels of hyaluronic acid/alginate, comprising an ideally suited operation for extrusion-based 3D bioprinting. 66 The MXenes containing hydrogel bioinks showed remarkable rheological characteristics, permitting the preparation of layered 3D structures with shape preservation and significant resolution. Additionally, these nanosheets within the hyaluronic acid/ alginate hydrogels bestowed electrical conductivity to the ink, demonstrating the inadequate electrical conductivity of the present bioinks that misallign with the physicochemical characteristics of the tissue.…”
Section: Ti 3 C 2 Mxenesmentioning
confidence: 99%
“…Additionally, these nanosheets within the hyaluronic acid/ alginate hydrogels bestowed electrical conductivity to the ink, demonstrating the inadequate electrical conductivity of the present bioinks that misallign with the physicochemical characteristics of the tissue. 66 Importantly, the condensed human embryonic kidney 293 cells inked by the MXene nanocomposite showed outstanding cell viability (more than 95%) in both the 3D bioprinted structures and the bulk hydrogel. 66 Additionally, smart zero-dimensional biocompatible Ti 3 C 2 T x MXene QDs have been prepared with precise surface changes for subcellular nanomedicine applications; 67 they were spontaneously uptaken into human endothelial cells within 24 hours of cell culture and their localization was remarkably stable with no detectable alterations in cellular morphologies.…”
Section: Ti 3 C 2 Mxenesmentioning
confidence: 99%
“…Using this technique is favorable in tissue engineering applications due to the ability to fabricate patterned tissue constructs with multiple cell types at the desired location, mimic the complex structure of the native tissue, and to simplify the crisis of the organ shortage. [ 209 ] Despite the beneficial aspects of the conductive materials for tissue regeneration in vitro, it is reported that the inherent properties of these materials could be changed when implanted in vivo, thus causing toxicity and activating the immune responses. The changes in the structural and physiological properties of the conductive materials in vivo restrict their applications in the clinic.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%